Subsidence and Effective Stresses Distribution Using Finite Element Techniques for an Iraqi Oilfield - Faraj, Ali K.; Salih, Ameen K.; Abdul Hussein, Hassan A.; Abed Al-Hasnawi, Ali N. (Journal of Petroleum Research and Studies, 2024)
Geomechanical problems are the most important problems that happen in the Zubair oil field; treating these problems requires a lot of time (Non-Productive Time) and thus increases the cost of drilling the well. Wellbore instability, subsidence, reservoir compaction, casing smash, pipe damage, and well kick is the main geomechanical problems facing the drilling process in the Mishrif formation, Zubair oilfield. The main goals of this study are to estimate the changes in stresses and subsequent subsidence values for this field during the production and injection periods. These estimation values, many problems can be avoided, thus increasing the drilling efficiency. This study is to introduce the one way coupling between the reservoir model and geomechanical model using the finite element method. The finite element technique in CMG 2018 program was used to estimate the stress states during the production or injection operations in this field of interest. The results of the 3D finite element model showed that the effective vertical stress rises by 32 psi during production while the effective horizontal stress increases by 16 psi. This may be explained by the fact that variations in pore pressure have little or no impact on the total vertical stress generated by weight. The results of this study demonstrated that the finite element method is a conservative method for coupling reservoir geomechanics and fluid flow. Subsidence values were 6.096 mm in the north part of the Al-Hammar dome, while at the center the subsidence was -5.1816 mm. Shuaiba dome has negative subsidence which is about -9.75 mm. It is important to note that the positive results subsidence signify the pore volume compacting, which may have an impact on the permeability and porosity of the reservoir petrophysics. As a result of a negative subsidence deformation, different failures including well casing damage, wellbore failure, and pipe smashing, are expected. Based on these results, production can cause an increase in the differential stress, which leads to rock shear failure and in injection cases, increasing pore pressure can cause a tensile rock failure.